Magnetised winds in transition discs: I. 2.5D global simulations - Martel, Étienne; Lesur, Geoffroy (Astronomy and astrophysics (Berlin), 2022)
Context. Protoplanetary discs are cold, dense, and weakly ionised environments that witness planetary formation. Among these discs, transition discs (TDs) are characterised by a wide cavity (up to tens of au) in the dust and gas distribution. Despite this lack of material, a considerable fraction of TDs are still strongly accreting onto their central star, possibly indicating that a mechanism is driving fast accretion in TD cavities. Aims. The presence of radially extended ‘dead zones’ in protoplanetary discs has recently revived interest in magnetised disc winds (MDWs), where accretion is driven by a large magnetic field extracting angular momentum from the disc. We propose that TDs could be subject to similar disc winds, and that these could naturally explain the fast-accreting and long-lived cavities inferred in TDs. Methods. We present the results of the first 2.5D global numerical simulations of TDs harbouring MDWs using the PLUTO code. We imposed a cavity in the gas distribution with various density contrasts, and considered a power-law distribution for the large-scale magnetic field strength. We assume the disc is weakly ionised and is therefore subject to ambipolar diffusion, as expected in this range of densities and temperatures. Results. We find that our simulated TDs always reach a steady state with an inner cavity and an outer ‘standard’ disc. These models also maintain an approximately constant accretion rate through the entire structure, reaching 10 −7 M ⊚ yr −1 for typical surface density values. The MDW launched from the cavity is more magnetised and has a significantly larger lever arm (up to 10) than the MDW launched from the outer disc. The material in the cavity is accreted at sonic velocities, and the cavity itself is rotating at 70% of the Keplerian velocity due to the efficient magnetic braking imposed by the MDW. Overall, our cavity matches the dynamical properties of an inner jet emitting disc (JED) and of magnetically arrested discs (MADs) in black-hole physics. Finally, we observe that the cavity is subject to recurring accretion bursts that may be driven by a magnetic Rayleigh-Taylor instability of the cavity edge. Conclusions. Some strongly accreting TDs could be the result of magnetised wind sculpting protoplanetary discs. Kinematic diagnostics of the disc or the wind (orbital velocity, wind speeds, accretion velocities) could disentangle classic photo-evaporation from MDW models.